Harmonisasi Fiqh Waris Islam dengan Hukum Positif di Indonesia - Sofyan, Aa (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
This study aims to explore the harmonization between Islamic inheritance law and positive law in Indonesia, within the context of a pluralistic society. Islamic inheritance law is strongly based on the Qur'an and Hadith, while Indonesia's positive law is governed by the Civil Code (KUHPer) and various other regulations. The fundamental differences between these two legal systems often lead to uncertainty and injustice in the distribution of inheritance, particularly regarding gender issues and the inheritance rights of non- Muslim heirs. Using a qualitative approach and descriptive-analytical methods, this research identifies the differences and similarities between Islamic inheritance law and positive law, while also analyzing the efforts made toward harmonization. Data was collected through literature reviews, interviews with legal experts, and legal document analysis. Content analysis techniques were used to identify key themes relevant to the harmonization of the two legal systems. This research is expected to provide policy recommendations that can strengthen the harmonization of inheritance law in Indonesia, aiming to create a fair, relevant, and contextually appropriate legal system for a pluralistic society. The study also hopes to contribute to improving public understanding of the importance of legal harmonization in maintaining social justice and reducing conflicts related to inheritance distribution.